2009
DOI: 10.1623/hysj.54.4.690
|View full text |Cite
|
Sign up to set email alerts
|

What impact will climate change have on rural groundwater supplies in Africa?

Abstract: One of the key uncertainties surrounding the impacts of climate change in Africa is the effect on the sustainability of rural water supplies. Many of these water supplies abstract from shallow groundwater (<50 m) and are the sole source of safe drinking water for rural populations. Analysis of existing rainfall and recharge studies suggests that climate change is unlikely to lead to widespread catastrophic failure of improved rural groundwater supplies. These require only 10 mm of recharge annually per year to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(79 citation statements)
references
References 34 publications
0
74
0
1
Order By: Relevance
“…Meeting regional water needs will thus depend on how water resources are understood, developed and most importantly, managed (MacDonald et al 2009(MacDonald et al , 2010. By 2005, it was reported that to meet Millennium Development Goals (MDG) on water, Tanzania needed to drill 14 000 SDWs and 1 500 boreholes per year (Baumann et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Meeting regional water needs will thus depend on how water resources are understood, developed and most importantly, managed (MacDonald et al 2009(MacDonald et al , 2010. By 2005, it was reported that to meet Millennium Development Goals (MDG) on water, Tanzania needed to drill 14 000 SDWs and 1 500 boreholes per year (Baumann et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Regional failure of an aquifer is unlikely, though increased demand may cause localized failure at a particular source of water. Unfortunately, few data exist upon which to base extraction policies (MacDonald et al, 2009). Declines of groundwater due to drought, rather than abstraction, have been observed in the Khalahari Karoo/Stampriest Artesian Aquifer and Lake Chad Basin Aquifer System (Scheumann and Alker, 2009).…”
Section: Path Forwardmentioning
confidence: 99%
“…Groundwater is the main source of water for much of the rural population of sub-Saharan Africa, particularly those in the drought-prone semi-arid regions (Foster et al, 2000;JMP, 2008;MacDonald et al, 2009;MacDonald et al, 2012). The exploitation and sustainability of this resource is key to human survival and economic development.…”
Section: Introductionmentioning
confidence: 99%